Nonlinear Matrix Ferroelectric Composites on Construction Quality and Safety Measures. (22nd August 2022) - Hu, Danping; Yan, Gongxing; Sun, Hongquan
Abstract : With the continuous emergence of concrete construction projects such as long-span bridges, high-rise buildings, nuclear power plants, and offshore platforms, researchers at home and abroad have made great progress in construction quality and safety measures in recent years. Construction quality is the main factor affecting the appearance and function of the building. Compared with traditional building construction materials, it has indeed made great improvements in organization and performance. For example, for nonlinear matrix ferroelectric composites, this functional material can better solve the problem of poor compatibility between general composites and concrete structural materials. It is not sensitive to humidity and can work in a concrete environment for a long time. These materials are indeed popular in building construction, various materials complement each other in performance and produce a synergistic effect so that the comprehensive performance of composite materials is better than the original composition materials and meets various high-quality requirements. But some properties are still not very clear. Therefore, this study mainly studies the influence laws of viscoelasticity, elastic viscoplasticity, and macro mechanical behavior of nonlinear matrix ferroelectric composites. Through theoretical analysis and experiments, it is concluded that the change of effective stress relaxation stiffness of nonlinear matrix ferroelectric composites tends to be stable with the increase of time, and the effective stress relaxation stiffness of composites increases with the increase of age volume fraction at t  = 0 s.